A 3D dislocation dynamics analysis of the size effect on the strength of [1 1 1] LiF micropillars at 300K and 600K. (22nd February 2016) - Chang, Hyung-Jun; Segurado, Javier; Molina-Aldareguía, Jon M; Soler, Rafael; LLorca, Javier
Abstract: The mechanical behavior in compression of [1 1 1] LiF micropillars with diameters in the range 0.5 μ m to 2.0 μ m was analyzed by means of discrete dislocation dynamics at ambient and elevated temperature. The dislocation velocity was obtained from the Peach–Koehler force acting on the dislocation segments from a thermally-activated model that accounted for the influence of temperature on the lattice resistance. A size effect of the type 'smaller is stronger' was predicted by the simulations, which was in quantitative agreement with previous experimental results by the authors [001 ]. The contribution of the different physical deformation mechanisms to the size effect (namely, nucleation of dislocations, dislocation exhaustion and forest hardening) could be ascertained from the simulations and the dominant deformation mode could be assessed as a function of the specimen size and temperature. These results shed light into the complex interaction among size, lattice resistance and dislocation mobility in the mechanical behavior of μ m-sized single crystals.